Management of Nematodes and Soil Fertility with Sunn Hemp Cover Crop - Koon-Hui Wang; Robert McSorley (EDIS)
Sunn hemp, Crotalaria juncea L. is a rapidly growing crop that is used for fiber production in India and Pakistan. It is most popular as a green manure in many tropical and subtropical areas in the world as an organic nitrogen source. Recently, there is a growing interest in rotating sunn hemp with cotton in the southern United States and in using sunn hemp as a summer cover crop in Florida and other southeastern states. Sunn hemp suppresses weeds, slows soil erosion, and reduces root-knot nematode populations (Rotar and Joy, 1983). When plowed under at early bloom stage, nitrogen recovery is the highest. This document is ENY-717, one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date first printed: September 2004.